Perception towards work life balance among public higher learning institutions in Kota Samarahan / Alwani Abdul Rahman & Nursharmina Lilek - Abdul Rahman, Alwani; Lilek, Nursharmina (2014)
Study on Work Life Balance (WLB) mostly published from Anglo-Saxon and Western countries such as US compared to Malaysia. There was very limited work published by Malaysian. Moreover, less concern from the government of Malaysia also contributed to low attribution on WLB concepts and alternatives among public sector. Therefore, the main purpose of this study is to determine the current level of WLB's achievement among public servants in three (3) selected public higher learning institutions in Kota Samarahan. Next, the identification of dominators of individual factors and organisational factors that affected the public servants to balance between work and life. From both factors, researchers need to identify whether both factors can be influencing the achievement of WLB. Finally, the next purpose is to identify if gender's role can influenced the WLB status among the public servants. Public servants here refer to both academic staff and non-academic staff from three public higher learning institutions. Findings were based on 145 respondents’ data analysis. The study highlighted that level of WLB achievement among public servants almost high, that means good. Both factors of individual and organisation have significance relationship in balancing work life, meanwhile individual factors is dominator. Plus, gender’s role is able to influence efforts to gain WLB among employees that can leads to gender conflict if not wisely managed. In short, awareness on WLB’s concepts, programme and policy must be increased as can give benefits to the organisation as well the individual.